2016
DOI: 10.1117/1.jbo.21.11.116001
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of topographic changes in the surface of back of young patients monitored for idiopathic scoliosis: correlation with radiographic variables

Abstract: Idiopathic scoliosis requires a close follow-up while the patient is skeletally immature to detect early progression. Patients who are monitored by radiographs are exposed to high doses of ionizing radiation. The purpose of this study is to evaluate if an optic noninvasive method of back surface topography based on structured light would be clinically useful in the follow-up of young patients with idiopathic scoliosis. This could reduce the number of radiographs made on these children. Thirty-one patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(46 citation statements)
references
References 28 publications
0
45
0
Order By: Relevance
“…The total sample size of the eight included studies consisted of 1 141 645 participants, with the age range of 7–21 years. The systematic review showed studies using MT among healthy children [ 25 27 , 30 , 31 ] and with scoliosis [ 24 , 28 30 ]. In all research enrolled as well as girls and boys.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The total sample size of the eight included studies consisted of 1 141 645 participants, with the age range of 7–21 years. The systematic review showed studies using MT among healthy children [ 25 27 , 30 , 31 ] and with scoliosis [ 24 , 28 30 ]. In all research enrolled as well as girls and boys.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies investigated both validity and reliability [ 26 , 29 , 30 ]. The repeatability of the MT examination was assessed based on the value of intraobserver and interobserver error [ 26 ] and Interclass Correlation Index [ 28 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exclusion criterion was based on the SHS parameter. Although this parameter is well established in Surface Topography (ST) measurements [26,27,60,65,66,67,68], literature does not provide specific cut-off values for faulty posture. Thus, subjects with outlier values of the SHS distribution in any of the measurements were suspected of having a faulty posture and were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…Weitkunat et al [8] used two standing lateral radiographs of the whole body taken using a biplanar low-dose radiographic imaging system (EOS Imaging, Paris, France). Comparing radiological methods and surface topography is a big challenge due to the differences in the imaged structures [25,26,27]. The unified interpretation of the results for various methods remains difficult.…”
Section: Introductionmentioning
confidence: 99%